2020
DOI: 10.2147/ppa.s251812
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patients’ Preference for Long-Acting Injectable versus Oral Antipsychotics in Schizophrenia: Results from the Patient-Reported Medication Preference Questionnaire</p>

Abstract: Introduction Understanding patients’ preferences for long-acting injectable (LAI) or oral antipsychotics (pills) could help reduce potential barriers to LAI use in schizophrenia. Methods Post hoc analyses were conducted from a double-blind, randomized, non-inferiority study (NCT01515423) of 3-monthly vs 1-monthly paliperidone palmitate in patients with schizophrenia. Data from the Medication Preference Questionnaire, administered on day 1 (baseline; open-label stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…An important argument for the switch was that PP1M and PP3M involved the same active component, and that frequency was the main difference. This is in line with the findings in Lai and Margolese [23] and a recent large-scale patient-reported questionnaire study [21]. The results also showed that most switches from PP1M to PP3M were recommended by the patients' health care providers, and that trusting the professionals was imperative for this decision.…”
Section: Results Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…An important argument for the switch was that PP1M and PP3M involved the same active component, and that frequency was the main difference. This is in line with the findings in Lai and Margolese [23] and a recent large-scale patient-reported questionnaire study [21]. The results also showed that most switches from PP1M to PP3M were recommended by the patients' health care providers, and that trusting the professionals was imperative for this decision.…”
Section: Results Discussionsupporting
confidence: 89%
“…In contrast, a recent large scale post-hoc analysis of patients medication preference and a multi-country questionnaire study reported that patients had a higher inclination to prefer PP3M over PP1M due to convenience and better control [21,22]. This was supported by the results from interviews with 14 patients, showing that PP3M was perceived as more convenient and with benefits when compared to PP1M [21][22][23]. So far, when investigating patients' perspectives, most studies have used questionnaires on health-related quality of life and patient satisfaction and have not utilized the potential of qualitative research methods.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study makes significant contributions to the current field of mental health and the treatment of LAI. First of all, unlike most previous clinical studies based on patients in psychiatric hospitals ( 59 , 60 ), this study is on a natural sample population of community patients. And before confirming the sample, investigators don't know whether respondents have been treated with LAI or oral medication.…”
Section: Discussionmentioning
confidence: 99%
“…56 Another study asked patients if they preferred LAI or oral medications; none of the patients preferring LAIs said that their preference was because LAIs were "less embarrassing," while 46% of patients who preferred oral medications chose this reason. 70 A further study comparing self-stigma between patients taking LAIs and oral medications found no significant differences in any ISMI domains between the two groups. 71 Studies investigating the differing perspectives of HCPs versus patients reported similarly conflicting results.…”
mentioning
confidence: 90%